Tectonomagmatic evolution of the volcano vent cluster of the Tzirate Range in Mexico - Mario E. Boijseauneau-López; Giovanni Sosa-Ceballos; Daniel Tapia-Flores; Antonio Pola; José Luis Macías; Miguel E. Castillo-Rodríguez; Xavier Bolós (Bulletin of Volcanology, 2026)
The Tzirate Range (TR; 1.5–0.93 Ma) is a volcanic vent cluster within the Michoacán-Guanajuato Volcanic Field (2.5 Ma–present), composed of effusive andesitic to rhyolitic rocks that reflect complex, multi-stage magmatic evolution. By integrating geochemical, mineralogical, isotopic, and morpho-structural data, this study reveals that magma differentiation in the TR was driven by fractional crystallization, magma mixing, and assimilation of crustal material within shallow reservoirs, under tectonic control exerted by the reactivation of basement faults. The rocks exhibit a calc-alkaline affinity with elevated δ 1 ⁸O values (+ 7.23 to + 9.43) and isotopic signatures (⁸⁷Sr/⁸⁶Sr = 0.70370–0.70431; εNd = 1.82–4.27 ± 0.33, 1σ), consistent with crustal contamination. Disequilibrium textures (e.g., resorption rims, patchy zoning) and mineral compositions (An 39–60 , En 43–79 ) reflect open-system processes and dynamic magma evolution. Hydrothermal assimilation experiments support incorporation of granitic material at ~ 880–900 °C and ~ 180 MPa. In addition, morphometric analysis of drainage networks using knickpoint detection and normalized steepness index ( K sn ) enables the identification of reactivated basement faults that control the magmatic plumbing system. Therefore, it demonstrates the utility of K sn -based morphometric analysis as a robust and complementary tool for identifying hidden tectonic systems in volcanic terrains with limited surface exposure. These findings suggest that the TR vent cluster represents a transitional stage between monogenetic and polygenetic volcanism, highlighting the influence of tectonic controls on vent distribution and long-term volcanic evolution. This interdisciplinary approach provides new insights into the mechanisms controlling the development and dynamics of volcanic clusters by characterizing their plumbing systems and structural frameworks.